Detection of Differentially Expressed Cleavage Site Intervals Within 3′ Untranslated Regions Using CSI-UTR Reveals Regulated Interaction Motifs - Harrison, Benjamin J.; Park, Juw Won; Gomes, Cynthia; Petruska, Jeffrey C.; Sapio, Matthew R.; Iadarola, Michael J.; Chariker, Julia H.; Rouchka, Eric C. (Frontiers in Genetics, 2019)
The length of untranslated regions at the 3’ end of transcripts (3’UTRs) is regulated by alternate polyadenylation (APA). 3’UTRs contain regions that harbor binding motifs for regulatory molecules. However, the mechanisms that coordinate the 3’UTR length of specific groups of transcripts are not well understood. We therefore developed a method, CSI-UTR, that models 3’UTR structure as tandem segments between functional alternative-polyadenylation sites (termed cleavage site intervals – CSIs). This approach facilitated 1) profiling of 3’UTR isoform expression changes and 2) statistical enrichment of putative regulatory motifs. CSI-UTR analysis is UTR-annotation independent and can interrogate legacy data generated from standard RNA-Seq libraries. CSI-UTR identified a set of CSIs in human and rodent transcriptomes. Analysis of RNA-Seq datasets from neural tissue identified differential expression events within 3’UTRs not detected by standard gene-based differential expression analyses. Further, in many instances 3’UTR and CDS from the same gene were regulated differently. This modulation of motifs for RNA-interacting molecules with potential condition-dependent and tissue-specific RNA binding partners near the polyA signal and CSI junction may play a mechanistic role in the specificity of alternative polyadenylation. Source code, CSI BED files and example datasets are available at: https://github.com/UofLBioinformatics/CSI-UTR